Flame retardant properties of polyamide 6 with piperazine pyrophosphate. (28th May 2017) - Xiao, Xiong; Zhai, Jinguo; Chen, Tao; Mai, Yongyi; Hu, Shuang; Ye, Wen; Xu, Xiaoli; Li, Pingyang; Lin, Zhuoshi; Yin, Liang
ABSTRACT: Piperazine pyrophosphate (PAPP) was mixed in polyamide 6 (PA6) to investigate its flame retardant properties. The PAPP was characterised by Fourier transform infrared (FT-IR), elemental analysis, proton nuclear magnetic resonance (1H-NMR) spectroscopy and thermogravimetric analysis (TGA). The elemental analysis and TGA results of PAPP indicated it had a high P element content and good thermal stability. The flame retardancy of PA6/PAPP was also characterised by TGA, limiting oxygen index (LOI), UL-94 vertical test and microscale combustion calorimetry (MCC). The TGA results showed that the PAPP increased the stability of the PA6/PAPP and resulted in a significant increase of char residue. PA6/PAPP passed the UL94 V-0 rating with a LOI value of 42 vol %. The MCC test indicated that the PAPP can greatly decrease the peak heat release rate (PHRR) and total heat release (THR). The results of scanning electron microscope (SEM) illustrated that PAPP can promote the formation of compact char layer.